Utilization of biofloc meal as a feed ingredient for Nile tilapia and common carp - Ekasari, Julie; Pasha, Hilda Kemala; Priyoutomo, Nur Bambang (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACTThis study was aimed to evaluate the utilisation of biofloc meal collected from biofloc-based catfish intensive culture as a mix ingredient for Nile tilapia Oreochromis niloticus and common carp Cyprinus carpio diet. A control diet containing 29.03% crude protein was used in this experiment. Experimental diet was made by mixing 30% biofloc waste meal with the control diet and repelleted after the addition of 2% of binder. To determine the experimental feed digestibility, 0.5% of Cr2O3 was added as a marker for digestibility. The feed was offered to satiation at a frequency of 3 times a day for 28 days of experimentation. Nile tilapia and common carp juveniles with an initial average body weight of 11.72±0.04 g and 8.81±0.04 g, respectively, were used as the experimental animals. Each fish species were randomly stocked with a density of 10 fish/aquarium (30´45´30 cm3). The results showed that dry matter digestibility of diets with 30 % biofloc waste meal in both fish species were significantly lower than those of the controls (P<0.05). However, protein, lipid and phosphorus digestibilities of diets containing biofloc waste meal were significantly higher than those of the controls (P<0.05). Feeding with biofloc waste meal mixed feed to tilapia resulted in lower growth rate compared to that to fed control feed. On the other hand, similar treatment to common carp resulted in comparable growth rate to the control treatment.Keywords: biofloc meal, digestibility, growth performance, tilapia, common carp ABSTRAK Penelitian ini bertujuan untuk mengevaluasi pemanfaatan tepung bioflok yang dikumpulkan dari limbah pemeliharaan ikan lele intensif berbasis teknologi bioflok sebagai campuran pakan untuk ikan nila Oreochromis niloticus dan ikan mas Cyprinus carpio. Pakan kontrol yang digunakan adalah pakan komersial dengan kadar protein 29,03%. Pembuatan pakan uji dilakukan dengan mencampurkan tepung limbah bioflok (30%) dengan pakan kontrol (67,5%) dan dibentuk pelet kembali setelah dilakukan penambahan binder sebanyak 2% dan Cr2O3 sebanyak 0,5% sebagai penanda untuk menganalisis kecernaan pakan dengan tepung limbah bioflok. Pakan diberikan secara at satiation dengan frekuensi pemberian pakan 3 kali/hari selama 28 hari pemeliharaan. Bobot rata-rata ikan awal adalah 11,72±0,04 g untuk ikan nila, dan 8,81±0,04 g untuk ikan mas dengan kepadatan awal masing-masing 10 ekor/akuarium (30´45´30 cm3). Hasil penelitian ini menunjukkan bahwa nilai kecernaan total pakan dengan tepung limbah bioflok baik pada ikan nila maupun ikan mas lebih rendah daripada pakan kontrol (P<0,05). Namun demikian, kecernaan protein, lemak, dan fosfor pakan dengan campuran tepung limbah bioflok lebih tinggi daripada kontrol (P<0,05). Pemberian tepung limbah bioflok sebanyak 30% sebagai campuran pakan menghasilkan laju pertumbuhan spesifik ikan nila yang lebih rendah (P<0,05), sedangkan perlakuan yang sama pada ikan mas memberikan laju pertumbuhan spesifik yang tidak berbeda nyata dengan kontrol (P>0,05). Kata kunci: tepung limbah bioflok, kecernaan, kinerja pertumbuhan, ikan nila, ikan mas